2019
DOI: 10.1021/acs.jpcc.8b11374
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Porphyrin–Graphene Oxide Nanohybrids: The pH-Dependent Behavior

Abstract: Noncovalent nanohybrids between meso-(phydroxyphenyl)porphyrin (TPPH) and graphene oxide (GO) sheets were studied as a function of pH. The overall charge of the TPPH molecule changes between negative (−4), neutral, and positive (+2) depending on the pH of the solution. Results of Fourier transform infrared spectroscopy, thermogravimetric analysis, and elemental analysis confirm successful noncovalent functionalization of GO sheets with TPPH. We applied a number of methods to probe the ground-state as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 59 publications
4
55
0
Order By: Relevance
“… 38 , 42 , 46 , 47 Theoretical calculations predict that only a 30° change in the orientation of the meso-substituents toward the porphyrin core can result in a bathochromic shift of the Soret band by as much as 30 nm. 48 Our previous calculations have shown that the interaction of ZnTPPH and TPPH with GO leads to a twisting of the side rings relative to the porphyrin core from about 60° to 45° and 39° for ZnTPPH and TPPH, respectively, 38 , 47 confirming the flattening of the porphyrin upon complexation. Moreover, the experimentally observed Soret band red shift of 16 nm for the ZnTPPH adsorbed on the GO surface was well reproduced in theory.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 38 , 42 , 46 , 47 Theoretical calculations predict that only a 30° change in the orientation of the meso-substituents toward the porphyrin core can result in a bathochromic shift of the Soret band by as much as 30 nm. 48 Our previous calculations have shown that the interaction of ZnTPPH and TPPH with GO leads to a twisting of the side rings relative to the porphyrin core from about 60° to 45° and 39° for ZnTPPH and TPPH, respectively, 38 , 47 confirming the flattening of the porphyrin upon complexation. Moreover, the experimentally observed Soret band red shift of 16 nm for the ZnTPPH adsorbed on the GO surface was well reproduced in theory.…”
Section: Resultsmentioning
confidence: 99%
“… 38 The slightly smaller red shift observed for ZnTMPyP in comparison to TMPyP upon adsorption on GO ( Figure S11 ) can be attributed to less profound flattening of the ZnTMPyP as observed previously for the TPPH and ZnTPPH. 38 , 47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…%) of the porphyrin onto GO. [157,159] CV The CV curves reveal that GO/porphyrin hybrids can act as good electrode materials for the electrocatalytic oxidation of other species, such as hydrazine or dopamine. The oxidation may occur at lower oxidation potential and higher oxidation peak current.…”
Section: Techniquementioning
confidence: 99%
“…[158] More recently, Gacka et al have described the preparation of non-covalent hybrids between 5,10,15,20-tetrakis(4-hydroxyphenyl)porphyrin (TPPH) and GO sheets at different pH values (Scheme 11). [159] While TPPH at neutral pH does not possess any charge, the protonation of its inner imino N atoms increases its charge to + 2, and the deprotonation of the À OH groups in the substituents decreases its charge to À 4. At acidic pH, the interaction of TPPH 2 + with GO was found to be stronger and it was largely suppressed at basic pH.…”
Section: Tgamentioning
confidence: 99%